Where next for research on fixation, inspiration and creativity in design?. (May 2017) - Crilly, Nathan; Cardoso, Carlos
Abstract : This is a report from an international workshop focused on the future of design fixation research within the broader context of work on creativity and inspiration. Fixation studies have already generated many useful results but there are clear opportunities to better connect with work done on other related concepts and work done in other disciplines. This would allow fixation research to broaden and strengthen its methodological approaches, offering richer insights into how design ideas originate and how they subsequently evolve. Such knowledge could then be applied to influence the development of design education, training and tools. In this way, fixation research would maximize its potential to provide insights into the creative process, improve design practice and thereby support innovation. Highlights: Design fixation affects a broad range of design practices. Fixation can be related to many other concepts from other disciplines. The relationship between fixation and creativity depends on the level of analysis. New methods should be developed for studying fixation in the lab and in the wild. Fixation research should shape the development of design tools and design training.